Should We Ever Pace for Carotid Sinus Syndrome? - Parry, Steve W. (Frontiers in Cardiovascular Medicine, 2020)
Carotid sinus syndrome has been associated with transient loss of consciousness for millennia, and while steeped in cardiovascular lore, there is little in the way of solid evidence to guide its main treatment modality, permanent cardiac pacing. This article reviews the history of the condition in the context of its contemporary understanding before examining three key concepts in the consideration of what constitutes a manageable disease: first, is there a pathophysiologic rationale for the disease (in this case carotid sinus syndrome)? Second, is there a good diagnostic test that will identify it reliably? And finally, is there a convincingly evidence-based treatment for the disease? Relevant literature is reviewed, and recommendations made in how we view pacing in the context of this intriguingly opaque condition.